The Impact of Social Media on Social Comparison and Self-Esteem - Utama, Atika Widya; Souza, Felipe; Costa, Bruna (Research Psychologie, Orientation et Conseil, 2025)
The ubiquitous presence of social media platforms has created an environment where individuals are constantly exposed to curated, idealized self-presentations. This environment is thought to intensify the natural human tendency for social comparison, which has significant implications for psychological well-being, particularly self-esteem. This study aimed to investigate the relationship between the intensity of social media use, the tendency for social comparison, and levels of self-esteem among young adults. A cross-sectional survey was conducted with a sample of 350 university students (aged 18-24). Participants completed validated instruments, including the Social Media Intensity Scale, the Iowa-Netherlands Comparison Orientation Measure (INCOM), and the Rosenberg Self-Esteem Scale. Correlation and mediation analyses were performed to test the hypothesized relationships. A significant positive correlation was found between the intensity of social media use and social comparison orientation (r = .45, p < .001). In turn, social comparison orientation was significantly negatively correlated with self-esteem (r = -.52, p < .001). Mediation analysis confirmed that social comparison significantly mediated the relationship between social media intensity and lower self-esteem. Intensive engagement with social media is strongly associated with a greater tendency for social comparison, which in turn predicts lower self-esteem. These findings highlight social comparison as a key psychological mechanism through which social media use may negatively impact mental health.